1992
DOI: 10.1042/bj2880319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin and phorbol esters on subcellular distribution of protein kinase C isoforms in rat adipocytes

Abstract: Effects of insulin and phorbol esters on subcellular distribution of protein kinase C (PKC) isoforms were examined in rat adipocytes. Both agonists provoked rapid decreases in cytosolic, and/or increases in membrane, immunoreactive PKC-alpha, PKC-beta, PKC-gamma, and PKC-epsilon. Effects of phorbol esters on PKC-alpha redistribution to the plasma membrane, however, were much greater than those of insulin. In contrast, insulin, but not phorbol esters, stimulated the translocation of PKC-beta to the plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
5

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 13 publications
3
51
5
Order By: Relevance
“…In previous studies, we examined the effect of phorbol ester (TPA), which can mimic in part the effect of DAG, the natural ligand for PKC (31). Phorbol esters activate conventional and novel PKCs immediately (32,33), but long term treatment with TPA results in a decrease in PKC in several cell types (34), mainly because of an increased rate of degradation of PKC protein (35,36). Because activation of PKC did not stimulate LPL, our data suggested that PKC plays a constitutive role in maintaining LPL synthesis.…”
Section: Pkc Isoformsmentioning
confidence: 67%
“…In previous studies, we examined the effect of phorbol ester (TPA), which can mimic in part the effect of DAG, the natural ligand for PKC (31). Phorbol esters activate conventional and novel PKCs immediately (32,33), but long term treatment with TPA results in a decrease in PKC in several cell types (34), mainly because of an increased rate of degradation of PKC protein (35,36). Because activation of PKC did not stimulate LPL, our data suggested that PKC plays a constitutive role in maintaining LPL synthesis.…”
Section: Pkc Isoformsmentioning
confidence: 67%
“…The adipocyte differentiation of 3T3L1 cells is known to be mediated through various signal transduction pathways by hormones, growth factors, and cytokines (Ailhaud, 1997;Kim et al, 2001;Koutnikova and Auwerx, 2001). Transcription factors, such as CCAAT/enhancer binding proteins and peroxisome proliferator-activated receptors were also found to be involved in adipocyte differentiation (Holst and Grimaldi, 2002), through many different signal transduction pathways, involving, phosphatidylinositol 3-kinase (PI3K), MAPKs, cAMP, steroid hormones, and protein kinase C (Farese et al, 1992;Frevert and Kahn, 1996;Engelman et al, 1998;Aubert et al, 1999). Of the inhibitors used to block specific signal transduction pathways, we found that NAC and LY 294002 effectively inhibited lipid droplet formation and MT-II induction during adipocyte differentiation in 3T3L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to find a critical signaling pathway involved in adipose differentiation in 3T3L1 cells, a variety of inhibitors, namely, PD 98059 (an MEK inhibitor) (Aubert et al, 1999), SB 203580 (a p38 kinase inhibitor) (Engelman et al, 1998), LY 294002 (a phosphatidyinositol 3-kinase inhibitor) (Gregoire et al, 1998), H9 (a protein kinase A and protein kinase C inhibitor) (Farese et al, 1992;Zhang et al, 2002), hydroxyurea (a G1/G0 arrest inhibitor) (Tang et al, 2003), and genistein (a tyrosine kinase inhibitor) (Harmon et al, 2002), and antioxidants (Mahadev et al, 2002), such as NAC, GSH, vitamin C, and retinoic acid, were pretreated and lipid droplet formation was estimated by oil red O staining. Notably, NAC and LY 294002 inhibited lipid droplet formation in 3T3L1 cells (Figure 3).…”
Section: Roles Of Mt-ii In the Adipocyte Differentiation Of 3t3l1 Prementioning
confidence: 99%
“…Its activation by insulin was noted early on in rat skeletal muscle tissues and adipocytes, as well as in HIRC-B cells and BC3H-1 myocytes [41,[115][116][117]. Like PKCβII, PKCε is also resistant to phorbol ester-induced down-regulation in HIRC-B fibroblasts, suggesting that PKCε resides in a specialized compartment in cells.…”
Section: Pkcεmentioning
confidence: 99%